Responsible stewardship of the environment: ecumenical and ethical antidotes for peace and eco-justice in Nigeria (2019)
The expectation of humans to live in a world that is peaceful has been a mirage because of their failure to recognise the nexus between justice and peace. It is no doubt that the concept of peace has taken central position in global conferences- political, economic or religious, yet, it seems people have only been paying lip-service to its realisation. Also, they fail to adequately address gender inequality, dehumanizing attitude of some stronger nations towards the weaker ones, and more significantly, the trending issue of the destruction of non-human creatures by humans. These factors among many others have orchestrated the tension that is being experienced in the cosmic order. This paper therefore advocates for mutual respect among humans irrespective of gender or race and responsible earth stewardship, especially by all Africans, so as to achieve peace in the society. Special emphasis has been placed on eco-justice considering its far-reaching significance to the restoration of peace. Sociological approach was adopted in gathering data that cut across many disciplines.